PERANAN KEYWORD (KATA KUNCI) DALAM IKLAN - Duto Hartanto, Deddi (Nirmana, 1999)
In the early 1996%2C Sanaflu launched the newest commercial ad themed Fireman. Most people will recognize and remember the words "Belum Tahu DiaÂ…." %2C a keyword that everybody : from children to older people of many classes in the society%2C certainly has repeated. Even a keyword is already concerned as something which can promote a product. Yet%2C not all keyword give advantages to product%2C keyword can be so familiar to everybody but is the products good in the selling market ? We often notice that keyword are usually put to compare products in the same kind%2C is this good ? This keyword thing is interesting to discuss in the topic of how far the role of a keyword in the success of commercial ad. Abstract in Bahasa Indonesia : Pada awal tahun 1996%2C Sanaflu meluncurkan iklan terbaru bertema pemadam kebakaran. Semua orang akan tahu dan ingat kalimat " Belum Tahu DiaÂ…" sebuah keyword (kata kunci) yang mulai anak kecil sampai orang tua dari berbagai golongan kelas ekonomi pasti pernah menirukannya. Bahkan keyword sudah dianggap sesuatu yang bisa mengangkat produk. Tidak semua keyword menguntungkan produk%2C keyword boleh terkenal tapi apakah produknya juga laku terjual ? Banyak kita jumpai keyword dijadikan suatu pembanding produk sejenis sesama kompetitor%2C apakah ini menguntungkan ? Keyword (kata kunci) inilah yang menarik untuk dibahas sampai sejauh mana peranannya dalam menunjang keberhasilan iklan.